Effectiveness of Muscle Energy Technique and Manipulation in The Management of Non-Specific Backache; A Randomized Control Trial: Effectiveness of Muscle Energy Technique - Khan, Salman; Sairien, Sairish; Talha , Muhammad; Maqbool, Lailma; Akbar, Aroosha; Kumar, Natesh; Salman, Muhammad (Pakistan Journal of Health Sciences, 2023)
Backache is the most common musculoskeletal impairment in general population worldwide. Objective: To evaluate the effectiveness of MET and manipulation in the management of non-specific backache. Methods: After getting the REC approval from The Neurocounsel Clinic, Islamabad this study was initiated. Duration of study was 6 months from September 20, 2022 to March 19, 2023. Simple convenient sampling technique was done for data collection and total 30 patients of both genders between age of 18-50 years old who had backache due to mechanical cause or had no comorbidity of any kind. Those patients who had a) Lumber disc disease, b) Spondylolisthesis, c) previous back surgery, d) cardiac disease, e) pain <3 on NPRS, f) Parkinson disease were excluded. Two equals (n=15 each) were formed named as group A (MET) and group B (Manipulation). 3 sessions/ week for 3 weeks were given to each group along with heating pad (10minutes). SPSS version-22 was used for data analysis. NP test was used for between groups analysis and level of significance was kept p<0.05. Results: The mean age of patients in group A was 28.25 ± 5.53 whereas of group B it was 34.73 ± 10.66. Between groups analysis revealed that there was no significant difference (p>0.05) between both groups. Conclusions: It was concluded from the result of current study that both MET and manipulation are equally effective in the pain reduction and QoL enhancement in NSLBP sufferers.